Implicit Rents from Own-Housing and Income Distribution: Econometric Estimates for Greater Buenos Aires - Leonardo Gasparini; Walter Sosa Escudero (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2004)
Most income studies do not take into account the implicit rent obtained by households who inhabit their own dwellings, a fact that introduces a potentially relevant bias in inequality, poverty, and welfare measures. In this paper we estimate these implicit rents for the Greater Buenos Aires area from information of Argentina's National Household Expenditures Survey (ENGH) of 1996/7. Based on a sample of households that rent their dwellings, quantile regressions are used to estimate observed rents from a hedonic model. Estimated coefficients are applied to households that do not rent their houses or apartments in order to predict the implicit rent derived from living in an owned house. Estimated implicit rents are added to the standard notion of household income and various inequality measures are reestimated. We find that the consideration of these implicit rents reduces inequality due to an income elasticity of spending in housing less than one, and to the relatively large proportion of house owners in the lower strata of the income distribution.
Keywords: D31; R21; 330; implicit rent; hedonic prices; quantile regression; housing; income distribution.